2022
DOI: 10.3389/fnume.2021.808627
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT and MRI in the Management of Multiple Myeloma: A Comparative Review

Abstract: During the last two decades, the imaging landscape of multiple myeloma (MM) has evolved with whole-body imaging techniques such as fluorodeoxyglucose positron emission tomography–computed tomography (18F-FDG PET/CT) and MRI replacing X-ray skeletal survey. Both imaging modalities have high diagnostic performance at the initial diagnosis of MM and are key players in the identification of patients needing treatment. Diffusion-weighted MRI has a high sensitivity for bone involvement, while 18F-FDG PET/CT baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…Further research is required to validate the use of volumetric BC measures from common anatomical CT regions to estimate true head‐to‐toe volumes and to compare accuracy to single lumbar slice surface areas. This ultimately could be achieved with regression modelling in a similar manner to the landmark study validating the single lumbar slice technique, 19 with true whole‐body PET‐CT used in multiple myeloma as a potential source of scans with true head‐to‐toe coverage 69 . However, a 2022 paper published after completion of this literature search makes progress towards this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research is required to validate the use of volumetric BC measures from common anatomical CT regions to estimate true head‐to‐toe volumes and to compare accuracy to single lumbar slice surface areas. This ultimately could be achieved with regression modelling in a similar manner to the landmark study validating the single lumbar slice technique, 19 with true whole‐body PET‐CT used in multiple myeloma as a potential source of scans with true head‐to‐toe coverage 69 . However, a 2022 paper published after completion of this literature search makes progress towards this question.…”
Section: Discussionmentioning
confidence: 99%
“…This ultimately could be achieved with regression modelling in a similar manner to the landmark study validating the single lumbar slice technique, 19 with true wholebody PET-CT used in multiple myeloma as a potential source of scans with true head-to-toe coverage. 69 However, a 2022 paper published after completion of this literature search makes progress towards this question. The authors trained a DL-model to segment volumetric BC from a 'whole body' PET CT.…”
Section: Comparison With True Whole-body Body Composition: Regional V...mentioning
confidence: 99%
“…As such, MRI is more sensitive and specific than other imaging methods such as conventional radiography, CT and PET, providing greater diagnostic accuracy without radiation exposure. This technique, however, has some disadvantages: it has limited availability, higher costs, less impact on clinical decision [18] and WB-MRI may have a long acquisition time (45 minutes to 1 hour), making it less prone to patient compliance and technical success. In order to promote standardization of WBMRI acquisition, interpretation and reporting, a Myeloma Response Assessment and Diagnosis System (MY-RADS) has been developed by an expert panel of radiologists, medical physicists and hematologists [19].…”
Section: Conventional Imaging Techniquesmentioning
confidence: 99%
“…A new hybrid technology combining PET and MRI has the potential to detect bone and extramedullary lesions through simultaneous metabolic and anatomic information [32]. Some studies have shown that 18 F-FDG-PET / MRI has the ability to detect medullary compression and bone lesions in patients with newly diagnosed SMM and newly diagnosed MM, with a higher diagnostic performance for MRI which detected focal lesions in 30% and 22% of PET-negative examinations [33]. Jamet et al also detected a higher performance of MRI in SMM compared to PET [9].…”
Section: Dynamic Contrast-enhanced Mrimentioning
confidence: 99%
See 1 more Smart Citation